การศึกษาแบบสุ่มของการให้สารอาหารทางหลอดเลือดดําต่อการเปลี่ยนแปลงภาวะทางโภชนาการในผู้ป่วยโรคไตระยะสุดท้ายที่ได้รับการฟอกเลือด - อธิภัทร์ บรรจงจิตร (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Background: Intradialytic parenteral nutrition (IDPN) is recommended for malnourished hemodialysis (HD) patients with a failure of oral nutrition supplements (ONS) trial. However, until now, there has been no randomized controlled trial revealing that IDPN reduced mortality or even improved in the predictor of mortality that was serum albumin compared with dietary counseling.Objective: To investigate the beneficial effects of IDPN on nutritional status in malnourished HD patients.Methods: This was a randomized controlled trial, comprising 3-month interventions and 3-month intervention-free phases. The malnourished HD patients were recruited and randomly assigned to receive either 3-in-1, omega-3-containing IDPN or intensive dietary counseling. The primary outcome was a change in serum albumin. The secondary outcomes were changes in serum prealbumin, muscle mass, muscle strength, composite nutritional scoring system assessed by malnutrition inflammation score (MIS) and 7-point subjective global assessment (SGA) and inflammatory biomarkers (interleukin-6 and high-sensitivity C-reactive protein).Results: A total of 38 patients were enrolled. 18 patients received IDPN. 20 patients received intensive dietary counseling. IDPN significantly increased serum albumin levels by 0.30 ± 0.20 g/dL (p=0.01) at month 3. The ratio of participants who were in 7-point SGA category A significantly increased in IDPN group at month 3 (50% to 70.6%; p=0.03). IDPN also improved MIS at month 3 (8.8 ± 3.8 to 6.8 ± 3.3 p=0.01). At month 6, the effects of previously administered IDPN on these outcomes decreased. In another group, there were no significantly changes in these outcomes. Serum prealbumin, muscle mass, muscle strength and inflammatory biomarkers remain unchanged in both groups throughout the study.Conclusions: 3-in-1, omega-3-containing IDPN significantly improved nutritional status that was serum albumin, 7-point SGA and MIS which are the predictor of mortality in maintenance HD patients compared with intensive dietary counseling.